(untitled) (Law and world, 2019)
Despite of the existence of foreign statutes, judgments, treatises and commentaries, or even “ofﬁcial” declarations or certiﬁcates, irreconcilable conﬂict will often arise in the acutely contested proceedings. Cases like these call for the opinions of experts of foreign law. Otherwise, it would seem that too much burden is put upon the court that is expected to determine foreign law without any external assistance when such situations arise. As the present paper suggests, applying to expert witnesses might be essential in a number of cases, they are even preferable in each single case. All misunderstandings concerning facts, differences in translations, ways of reasoning and basis for conclusions can be revealed by the direct, as well as, the cross-examination in the court with the presence of the parties. What is the most favorable role of an expert, whether appointed by parties or the court? It appears that an expert provides the reasoned support for a particular interpretation of foreign law and assists the counsel by responding on the submissions of any opposing experts.